2019
DOI: 10.31557/apjcp.2019.20.6.1921
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glutathione-S-Transferases M1 and T1 Deletional Variants with Development of Oral Squamous Cell Carcinoma: A Study in the South-East of Iran

Abstract: not specified yet (Dong et al., 2013). Glutathione-S-transferases (GST) are detoxifying enzymes participating in the neutralization of oxidative mediators within cells. GSTs belong to phase II detoxifying enzymes mediating conjugation of carbon, nitrogen or sulfur-containing molecules. In mammals, eight families

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
7
0
1
Order By: Relevance
“…[ 43 ] and Saravani et al . [ 44 ] Further, studies as that of Maurya et al, [ 40 ] Zakiullah et al . [ 41 ] and Dong et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] and Saravani et al . [ 44 ] Further, studies as that of Maurya et al, [ 40 ] Zakiullah et al . [ 41 ] and Dong et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 44 ] Moreover, several reports showed that GSTT1 gene increased the risk of certain types of cancer. [ 32 34 , 45 ] However, there is not a common rule, the disease protection effect of GSTT1 null genotype has also been found. [ 29 , 46 ] GSTT1 is associated with the metabolism of detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…GSTT1 null genotype and GSTM1 null genotype could lead to complete absence of the enzyme, [ 28 ] further increasing the risks of various diseases, such as diabetes, [ 29 ] male infertility, [ 30 ] hypertension, [ 31 ] and some types of cancer. [ 22 34 ] To date, many researches have indicated the correlation between SCZ and gene polymorphisms of GSTT1, GSTM1. [ 35 38 ] However, the results were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion polymorphism in GST genes (non-functional alleles) has been found to be associated with the development of certain types of cancer, such as oral cancer (Saravani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%